The Impact of Religiosity, Risk Tolerance, Financial Behavior, and Locus of Control on Sharia Investment Decisions: The Moderating Role of Financial Literacy - Hidayanti, Febriana; Tubastuvi, Naelati; Wahyuni, Sri; Santoso, Suryo Budi (Jurnal REKSA: Rekayasa Keuangan, Syariah dan Audit, 2025)
This research aims to examine the influence of religiosity, risk tolerance, financial behavior, and locus of control on Sharia investment decisions with financial literacy as a moderating variable. The sample consisted of 200 Islamic capital market investors in Indonesia, selected using convenience sampling. Data analysis used Partial Least Squares Structural Equation Modeling (PLS-SEM). The results of this study state that religiosity, risk tolerance, financial behavior, locus of control, and financial literacy have positive and significant effects on the Sharia investment decision. Financial literacy can moderate the influence of religiosity, risk tolerance, and locus of control on investment decisions. Financial literacy is proven to moderate the relationship between independent variables and Sharia investment decisions, increasing the positive influence of religiosity and financial behavior on investment decisions. This finding indicates that increasing financial literacy can strengthen Sharia investment decisions that are more rational and in accordance with religious principles. The practical implications of this study are important for policymakers to design financial literacy education programs that can improve public understanding of Sharia investment. Financial practitioners can consider religiosity and financial literacy factors in designing investment products that follow Sharia values ​​and can attract more diverse investors.